The involvement of accountants in corporate strategy in Malaysia: a stewardship theory perspective - Annuar, Hairul Azlan; Ismail, Yusof (Virtus Interpress, 2014)
The purpose of the research is to ascertain the extent and nature of accountants’ involvement in the formulation phase of corporate strategy in Malaysian public listed companies (PLCs). This is achieved using the triangulation approach consisting of survey questionnaires and interviews. The findings reveal that accountants in Malaysia are involved in the formulation phase of corporate strategy. At this stage, accountants appear to be discharging their stewardship role, and are involved even in the very initial stage of advising management with strategic proposals, directly helping to formulate proposals and even shaping the strategic framework, which ensure that only strategic proposals that lie within the current concept of strategy is submitted and deliberated.